L'article 7 de la Charte canadienne des droits et libertés et les principes de justice fondamentale - Duplé, Nicole (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
The author seeks to identify the different guarantees provided by the principle of fundamental justice under article 7 of the Canadian Charter of Rights and Freedoms as interpreted by the Courts. The importance of such guarantees varies depending on whether the Courts limit the application of the principle to procedural matters or consider them to be of wider application.